2021
DOI: 10.1016/j.ajog.2020.08.034
|View full text |Cite
|
Sign up to set email alerts
|

A specific bacterial DNA signature in the vagina of Australian women in midpregnancy predicts high risk of spontaneous preterm birth (the Predict1000 study)

Abstract: BACKGROUND: Intrauterine infection accounts for a quarter of the cases of spontaneous preterm birth; however, at present, it is not possible to efficiently identify pregnant women at risk to deliver preventative treatments. OBJECTIVE: This study aimed to establish a vaginal microbial DNA test for Australian women in midpregnancy that will identify those at increased risk of spontaneous preterm birth. STUDY DESIGN: A total of 1000 women with singleton pregnancies were recruited in Perth, Australia. Midvaginal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 97 publications
(104 reference statements)
0
43
1
4
Order By: Relevance
“…Despite these findings, we did not observe any relationship between L. iners dominance or any vaginal microbiota profile and subsequent risk of PTB in this cohort. This is in contrast to previous studies of predominantly Caucasian women by ourselves and others that have reported a relationship between L.iners and increased risk of PTB or cervical shortening, which is clinically used as a marker of PTB risk (6,7,12,48). Our data instead indicates that like Hispanic and African American women, L. iners does not appear to be risk factor for PTB in Chinese populations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite these findings, we did not observe any relationship between L. iners dominance or any vaginal microbiota profile and subsequent risk of PTB in this cohort. This is in contrast to previous studies of predominantly Caucasian women by ourselves and others that have reported a relationship between L.iners and increased risk of PTB or cervical shortening, which is clinically used as a marker of PTB risk (6,7,12,48). Our data instead indicates that like Hispanic and African American women, L. iners does not appear to be risk factor for PTB in Chinese populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Dominance of the vaginal niche by commensal Lactobacillus species is often considered "optimal" due to their ability to prevent pathogen colonisation through competitive exclusion, in part achieved through the production of antimicrobial compounds and production of lactic acid (4,5). Recent studies have highlighted L. crispatus dominance as being protective against preterm birth (PTB) (2,(6)(7)(8)(9) and neonatal sepsis following preterm prelabour rupture of membranes (1). By contrast, colonisation by L.iners (7,(10)(11)(12) or Lactobacillus species depleted, high diversity compositions are associated with an increased risk of PTB (2,7,9,10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2-27% of pregnant women, the microbiome composition shifts to an increase in species diversity, leading to a dysbiotic vaginal microbiome associated with a disease state. Several studies have now show that an increase in bacterial diversity is linked to reproductive tract inflammation and increased risk of PTB [15][16][17][18][19] . Despite numerous studies investigating the predictive usefulness of vaginal microbiome analysis, the diagnostic utility of this approach remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies investigating the predictive usefulness of vaginal microbiome analysis, the diagnostic utility of this approach remains elusive. In a recent large study of low-risk Australian women, a high-risk microbial profile in the 2nd trimester was identified based on the presence/absence and combinations of known bacterial species 18 . Notwithstanding this study's clinical relevance to PTB management, it is important to point out that this particular work is based on analysis of a selected number of risk-associated bacteria, not the entire microbiome per se.…”
Section: Introductionmentioning
confidence: 99%